Oh Canadá - Krugman, Paul (2000)
Those of us working in international monetary theory have been wondering for a decade when Robert Mundell would receive his well-deserved Nobel Prize in Economic Sciences. In this field, the contribution of the Canadian economist is so important, so “seminal” - a widely used adjective, but really appropriate in this case - that in many controversial aspects his ideas are the basis of all discussion. However, a layman might be confused about the exact reasons why Mundell received his award. Almost pathetically the editorial page of The Wall Street Journal has declared that this is a Nobel for "the supply side". There is no reason to be surprised: Robert Bartley, the publisher, tries to argue that intellectual exoneration has been a nearly desperate goal lately. After eight years of "Clintonian" expansion that makes Reagan's "seven fat years" wrinkled, and full of silly-looking supply theories, like Jude. Wanniski, The Wall Street Journal would accept whatever is at hand.